ANALISIS PENGARUH PEMBANGUNAN JALAN LINGKAR LUAR TIMUR SURABAYA TERHADAP NILAI TANAH DISEKITARNYA - Gigih Bambang Sutarji; I Nyoman Dita Pahang Putra; Anna Rumintang Nauli (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2021)
The increasing activity of the city of Surabaya has led to an increase in the need for transportation accessibility, therefore the city government of Surabaya has responded to these demands by building the Out East Ring Road (JLLT). The construction of the new access road is considered to have an effect and cause changes to several things in the surrounding area, one of which is the value of land. Therefore, this study was conducted to determine the magnitude of the influence caused by the construction of the JLLT. The areas that were the subject of this study consisted of 4 villages, namely Bulak, Tanah Kali Kedinding, Kedung Cowek, Tambak Wedi. The land value data used in this study were obtained from the Surabaya City Regional Financial and Tax Management Agency (BPKPD) which is then mapped according to the land value zone (ZNT) to obtain the average indicated value (NIR) each year so that it is ready for analysis. The analytical method used is linear regression to determine the influence of development on land values, while to see the pattern of changes using graph analysis. From the regression analysis, it was found that the influence of the construction of the JLLT was 6.28% and had a positive effect on the value of the land or if the distance to the location of the land was greater, the value would increase.